STATISTICAL ANALYSIS OF OVERHAUL OF APARTMENT BUILDINGS THAT INCREASE THE ENERGY EFFICIENCY OF BUILDINGS - L. A. Davletshina; A. V. Bezrukov (Вестник университета)
The subject of the study is major repairs of an apartment building. The authors analyse the concepts of “capital repairs of an apartment building” and “energy efficient repair”, explore the normative and methodical base. Based on the presented statistical data on the state of the apartment buildings, the paper proposes an original system of indicators for evaluating energy-efficient capital repairs. The assessment of the population by the degree of satisfaction with housing conditions is characterized by the data of a sample survey. The article uses data on the results of the implementation of regional programs of energy-efficient capital repairs in pilot regions, compares approaches to energy-efficient repairs, identifies similar parameters and regional features.